Diversity patterns of plant place names reveal connections with environmental and social factors. (September 2016) - Fagúndez, Jaime; Izco, Jesús
Abstract: There is a strong connection between cultural and biological diversity at a global scale, especially in the linguistic domain, but less is known at regional scales. Indicators of such reciprocity are found in the linguistic expression of natural elements, and their representation in the landscape through toponymy. Here we evaluate the geographic distribution of phyto-toponyms, places named after a native local flora, in Galicia, NW Spain. We created the concept of toponymic species (topo-species) for groups of places named after a plant taxon. By using different regression models assuming global effects of the variables (Ordinary Least Squares, OLS) or non-stationarity (Geographically Weighted Regression, GWR), we explored the connection of topo-species richness and diversity with environmental (river density, altitude and natural habitats density) and social (total density of toponyms, population density) factors. Topo-species richness and diversity were significantly correlated with the studied factors. Total density of toponyms, river density, altitude and natural habitats density showed significant positive values in the models, while population density had little or no effects. GWR performed better for all variables, especially for Shannon diversity index. We conclude that place names of natural elements depict human's interaction with the environment. They are stable, spatially-explicit elements that may be used as indicators of bio-cultural diversity. In addition, they represent an intangible cultural heritage that should also be preserved. Graphical abstract: Highlights: OLS and GWR regression analyses of places named after plants at a regional scale. New concept of toponymic species defined as places named after a biological taxon. Places named after plants spatially correlate with natural habitats, rivers, altitude. No correlation with population density, but strong with total number of toponyms. Toponyms of natural elements proposed as indicators of biocultural diversity.